1998
DOI: 10.1136/jnnp.65.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural disturbances, rehabilitation outcome, and lesion site in patients after rupture and repair of anterior communicating artery aneurysm

Abstract: Objective-To determine: (1) patterns of cognitive and psychiatric dysfunction; (2) those neurobehavioural parameters which mostly influence disability in activities of daily living (ADL) and handicap in occupational and psychosocial activities, and (3) underlying neuroanatomical pathology in patients after rupture and repair of anterior communicating artery (ACoA) aneurysm. Methods-30 patients were extensively examined by means of a comprehensive battery of neuropsychological tests, by rating of psychopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 29 publications
6
51
0
2
Order By: Relevance
“…25 Several neuropsychological studies, however, indicated that the lesions in the orbitofrontal area alone did not cause amnesia. 3,36,37 Alternatively, several reports attributed basal forebrain amnesia to interruption of the cholinergic system. 1,3,11,38 Indeed, in our patients, infarction in the paraterminal gyrus in 8 and in the diagonal band of Broca in 5 suggests likely involvement of the cholinergic system.…”
Section: Figmentioning
confidence: 99%
“…25 Several neuropsychological studies, however, indicated that the lesions in the orbitofrontal area alone did not cause amnesia. 3,36,37 Alternatively, several reports attributed basal forebrain amnesia to interruption of the cholinergic system. 1,3,11,38 Indeed, in our patients, infarction in the paraterminal gyrus in 8 and in the diagonal band of Broca in 5 suggests likely involvement of the cholinergic system.…”
Section: Figmentioning
confidence: 99%
“…Moreover, gyrus rectus resection caused focal encephalomalacia, but no consequences on the diverse neuropsychological evaluation were observed. In the literature, partial subpial resection of the gyrus rec tus during the pterional approach 53 to the ACoA aneurysm has not been reported to cause any adverse effects on neu robehavioral variables 5 or on QOL. 31 The choice of the side of approach did not cause any significant cognitive conse quences.…”
Section: Interdisciplinary Approach To An Acoa Aneurysmmentioning
confidence: 99%
“…5 In addition to the consequences of SAH in the subfrontal area, authors of some prospective studies (with level 3 evidence) have attempted to investigate the involvement of sac exclusion regarding outcome. It seems that the cog nitive outcome of patients treated by endovascular coiling was more favorable than that in those treated by micro surgical clipping.…”
Section: Neuropsychological Impairment After Treatment Of Acoa Rupturmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Controversy exists regarding the impact of anatomical location of the aneurysm on cognitive function after SAH. Early studies 21,[25][26][27] suggested patients with anterior communicating artery aneurysms are particularly susceptible to amnesia although recent reports 23,24,[27][28][29][30][31] failed to find a difference related to aneurysm location. Lack of standardized time of follow-up and small numbers of patients in some investigations potentially contributed to the differences.…”
Section: Discussionmentioning
confidence: 99%